Oral lactoferrin as a treatment of pediatrics’ anemia resulted from chronic kidney diseases: a randomized controlled trial - Sahar Kamal Hegazy; Mai Salah El-Din Koura; Mohamed Shokry Elharoun (Scientific Reports)
Abstract Anemia in pediatrics is often associated with chronic conditions such as chronic kidney disease (CKD). It can worsen the disease prognosis and affect quality of life. Injectable dosage forms are predominantly used in its treatment with various side effects. This randomized and parallel clinical trial aimed to compare the effectiveness of oral lactoferrin with intravenous (IV) iron dextran in managing anemia resulted from CKD in pediatrics. The study involved 60 children diagnosed with CKD-related anemia who were allocated into two separate groups. Group 1 consisted of 30 pediatric patients who received 100 mg of oral lactoferrin daily for a period of 3 months. Group 2 included 30 pediatric patients who were given IV iron dextran at a dosage of 50 mg three times weekly for 3 months. Both treatments are effective in treating CKD-induced anemia in pediatrics; however, oral lactoferrin demonstrated superior efficacy as there was a significant change within that group in levels of Hb, RBCs, MCH, iron, RDW-SD, MCHC, IL-6, and GDF-15 before and after treatment. In contrast, IV iron dextran showed significant changes within its group in iron, GFR, IL-6, GDF-15, and RDW-SD. After 3 months of treatment, no significant differences were observed between the two groups.